Bodies for battle : US Army physical culture and systematic training, 1885-1957 - Gatzemeyer, Garrett (Modern war studies., 2021)
"War is physical. In combat, fortune favors the soldier in better condition. Superior conditioning enables troops to fight longer and harder, to move farther and faster, to carry heavier loads and endure greater hardship. These relative advantages can be the difference between life and death, victory and defeat. In Bodies for Battle, Garrett Gatzemeyer investigates the creation and evolution of an official U.S. Army physical culture during the period when the most significant changes were made: 1885 to 1957. Using archival documents, training manuals, and professional journals serving military officers and physical educators, Gatzemeyer shows how, beginning in the late nineteenth century, officers drew on contemporary popular fitness culture and the professionalizing field of physical education to craft an associated system of exercise that has informed approaches to physical training in the U.S. Army ever since"--